Reinforced concrete design to eurocodes : design theory and examples - Bhatt, Prab; MacGinley, T.J. (Thomas Joseph); Choo, Ban Seng (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'This fourth edition of a bestselling textbook has been extensively rewritten and expanded in line with the current Eurocodes. It presents the principles of the design of concrete elements and of complete structures, with practical illustrations of the theory. It explains the background to the Eurocode rules and goes beyond the core topics to cover the design of foundations, retaining walls, and water retaining structures. The text includes more than sixty worked out design examples and more than six hundred diagrams, plans, and charts. It suitable for civil engineering courses and is a useful reference for practicing engineers.'--
'First published 1978 as Reinforced concrete : design theory and examples, by E&FN Spon ... 1978 [written by] T.J. MacGinley'--Title page verso.
Includes bibliographical references and index.
Keywords: Reinforced concrete construction; Reinforced concrete construction -- Standards -- Europe